Clinical outcome of cord blood transplantation for nine children with juvenile myelomonocytic leukemia receiving fludarabine‐busulfan‐cyclophosphamide‐based conditioning. (8th November 2021) - Li, Guifang; Sun, Zimin; Geng, Liangquan; Wan, Xiang; Zhu, Xiaoyu; Tang, Baolin; Tong, Juan; Yao, Wen; Song, Kaidi; Qiang, Ping; Zhang, Lei; Zhang, Xuhan; et al.
Abstract: Background: Juvenile myelomonocytic leukemia (JMML) is a rare hematological malignancy in young children and can only be cured through the allogeneic stem cell transplantation. Procedure: We have retrospectively analyzed the outcomes of nine children with JMML after unrelated cord blood transplantation (UCBT). Results: Eight patients who have received a myeloablative conditioning regimen of fludarabine (FLU), busulfan (BU), and cyclophosphamide (CY) have gotten engraftment. None of the nine patients has relapsed following initial UCBT. Six patients are still alive and in complete remission after UCBT with a median observation time of 43 months (range: 10–80 months). Conclusions: This study shows that UCBT with FLU‐BU‐CY conditioning regimen can represent a suitable option for children with JMML.